A Multi-objective Hybrid Heuristic Approach for Optimal Setting of FACTS Devices in Power System Operation - Sai Ram Inkollu; Venkata Reddy Kota (Institute of Advanced Engineering and Science, 2016)
Improvement of power system performance in terms of increased voltage profile and decreased transmission loss is becoming one of the challenging tasks to the system operators under open access environment. Apart from traditional power flow controlling devices, use of Flexible AC Transmission System (FACTS) devices can give an attractive solution for the operation and control of deregulated power system. The type, size, location and number of FACTS devices are to be optimized appropriately in order to get the targeted benefits. In this paper, two FACTS devices, Thyristor Controller Phase Shift Transformer (TCPST) and Interline Power Flow Controller (IPFC) are selected to obtain the required performance such as improvement of voltage profile and loss minimization. To search the optimal location and optimal rating of the selected FACTS devices, a hybrid algorithm which formulated with Particle Swarm Optimization (PSO) and Gravitational Search Algorithm (GSA) is proposed. At the first step, the optimization problem is solved for finding the optimal location of FACTS devices using PSO with an objective of voltage profile maximization and later GSA is implemented to optimize their parameters with an objective of transmission loss minimization. The proposed method is implemented on IEEE 30-bus test system and from the simulation results it can be proved that this technique is well suited for real-time application.